2010
DOI: 10.1088/0004-6256/139/6/2716
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “Vla Imaging of Virgo Spirals in Atomic Gas (Viva). I. The Atlas and the H I Properties” (2009, Aj, 138, 1741)

Abstract: Galaxy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
655
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(692 citation statements)
references
References 0 publications
34
655
3
Order By: Relevance
“…Recently a new VLA H I imaging survey of selected galaxies in the Virgo cluster (VIVA, VLA Imaging of Virgo spirals in Atomic gas) has been completed Chung et al 2009. This survey confirmed some already well known facts, e.g.…”
Section: The Other Extreme the Center Of Virgosupporting
confidence: 72%
“…Recently a new VLA H I imaging survey of selected galaxies in the Virgo cluster (VIVA, VLA Imaging of Virgo spirals in Atomic gas) has been completed Chung et al 2009. This survey confirmed some already well known facts, e.g.…”
Section: The Other Extreme the Center Of Virgosupporting
confidence: 72%
“…The spiral galaxies in the Ursa Major cluster do not show any prominent hint of HI deficiency or gas stripping (see Fig. 1 of Verheijen 2004), while many examples for ram pressure stripping are found in the Virgo cluster (e.g., Chung et al 2009). This is also supported by no detection of intracluster medium in the Ursa Major cluster (Verheijen & Sancisi 2001).…”
Section: Environmental Effects In a Lower Density Clustermentioning
confidence: 99%
“…This was exemplified in exquisite detail by the VLA 1 Imaging of Virgo in Atomic gas survey (VIVA; Chung et al 2009), which demonstrated the importance of the highest density environments in shutting down star formation via strong gas depletion mechanisms. Other observational (e.g.…”
Section: Introductionmentioning
confidence: 98%